DESAIN STRUKTUR DERMAGA TIPE JETTY PADA EMBUNG INDULUNG KOTA TARAKAN - Sulu, Wandi Toding; Prasetya, Noerman Adi (Civil Engineering Scientific Journal, 2024)
ABSTRACT : Indulung reservoir in Tarakan is crucial water distribution systems that provides clean water to the residents of Tarakan, especially in the eastern region. Besides its primary function as a water distributor, indulung reservoir has the potential to serve as a recreational area for community. This paper aims to design a jetty at understand the structural design and analysis of the jetty elements. The analysis was conducted using SAP 2000 v22 softwere to understand the structural design and analysis of the jetty elements. From the SAP 2000 analysis and reinforcement calculations, the designed slab has a width of 300 cm and a thickness of the 15 cm, reinforced with D 13 mm rebar at 200 mm intervals. For the beams, the analysis and calculations revealed the following congfigurations: for dimensions of the 25 x 40 cm, reinforcement wuth D 16 cm rebar, with supports n (-) = 5, n (+) = 3, field n (-) = 2, n (+) = 3; for dimensions of 35 x 45 cm, supports n (-) = 6, n (+) = 4, field n (-) =4, n (+) = 4; for dimensions of 40 x 50 cm, supports n(-) = 5, n (+) = 3, field n (-) = 2, n (+) = 3. The calculations of the pier dimensions yielded 110 x 110 x 50 cm and 120 x 120 x 60, with axial loads of 30 tons and 43 tons, reinforced with D 16 rebar, n = 6 pieces. The jetty’s pile foundation uses prefabricated piles from wika, with diameters of 50 cm and 60 cm, classified as type C, and load capacities of 17 tons and 29 tons, respectively. The maximum moment at the supports is 11,9 ton.m and at the span is 12,16 tons.m, with an axial force Pu 18,6 tons.Keywords : Jetty Pier, Jetty Design, Indulung Reservoir.ABSTRAK: Embung indulung  Tarakan  adalah  salah  embung  yang mendistribusikan  air bersih  kepada masyarakat kota tarakan terutama masyarakat dibagian wilayah Tarakan Timur. Disamping kegunaan sebagai penyalur air bersih, embung indulung Tarakan memiliki potensi sebagai objek wisata bagi masyarakat Kota Tarakan, untuk itu penulis mencoba untuk merencankan Dermaga pada embung ini. Analisis ini menggunakan software aplikas SAP 2000 v22 tujuan dari studi ini adalah untuk mengetahui bagaimana desain elemen struktur dan analisis struktur pada dermaga embung ini. Dari Hasil analisis SAP2000 dan Perhitungan penulangan pelat, didapatkan pelat dengan lebar 300 cm dan tebal 15 cm dengan tulangan D13 mm dan jarak 200 mm. Dari Hasil analisis SAP2000 dan perhitungan balok, didapatkan balok dengan tulangan D16 cm pada dimensi 25 x 40 cm, tumpuan n (-) = 5 buah, n (+) = 3, lapangan n (-) = 2 buah, n (+) = 3 buah. pada dimensi 35 x 45 cm, tumpuan n (-)= 6 buah, n (+) = 4, lapangan n (-) = 4 buah, n (+) = 6 buah. pada dimensi 40 x 50 cm, tumpuan n (-) = 5 buah, n (+) = 3, lapangan n (-) = 2 buah, n (+) = 3 buah. Dari Hasil Perhitungan Poer, didapatkan hasil pada dimensi poer 110 x 110 x 50 cm dan 120 x 120 x 60, dengan beban aksian 30 ton dan 43 ton didapat tulangan D16 dengan jumlah n = 6 buah. Dimensi Tiang pancang dermaga menggunakan pondasi tiang pancang fabrikasi dari wika dengan diameter 50 cm dan 60 cm dengan tipe class c dan crack 17 ton dan 29 ton. Momen yang terjadi pada Mu tumpuan terbesar 11,9 ton.m dan Mu lapangan12,16 ton.m, dengan gaya aksial Pu sebesar 18,6 ton.Kata kunci: Dermaga Embung,  Desain Dermaga, Embung Indulung.